Validity of Criticism of the Maudhu' Hadith: Comparative Study of Nashiruddin Albani and Syuhudi Ismail's Methodology - Sulis Nuriyawati; Muhammad Syaikhur Ridho (al-Afkar, Journal For Islamic Studies, 2026)
This study discusses the validity of maudhu’’ hadith criticism based on a comparative study of the methodologies of Nashiruddin Albani and Syuhudi Ismail. As contemporary hadith critics in the 20th century, they certainly have their own views on minor rules in determining the validity of the naqd al-Hadith. This is because the criteria for both minor rules in assessing the connection of the sanad and the justice and the shi'ifan of the narrator have the same elements. The similarity of these minor rules gives rise to the criteria of order in determining the validity of the hadith or judging the validity of the narrator and his narration. The purpose of this study seeks to explore the typology of the validity of both critics in validating the validity of the narrator and his narration. The academic anxiety that arises is how the validity of the maudhu’’ hadith criticism of these two figures in determining the authenticity and shi'ifan in the aspects of sanad and matan. This research method uses a qualitative study, namely descriptive-analytical, based on the main works of these figures in studying maudhu’’ hadith and its authenticity. The results of this comparative study of the two contributions indicate that Albani's strict criteria for interpreting hadith are classified as moderate criticism because his validity critical analysis is based on classical scholars' criticism and an evaluation of his research. Meanwhile, Syuhudi Ismail prioritizes the contextual aspect of matn (matan) after successful sanad research. Therefore, the two differ in their approaches to validating the validity of hadith.